L’intersectionnalité appliquée : un projet pilote à Montréal - Lacharité, Berthe; Pasquier, Anne (Nouvelles pratiques sociales, 2014)
Cet article est tiré de la présentation faite par Anne Pasquier (Table des groupes de femmes de Montréal) et Berthe Lacharité (Relais-femmes) dans le cadre du 6e Congrès international des recherches féministes francophones de Lausanne – Atelier 10 – Composer avec la complexité des rapports sociaux dans la vie des femmes : conceptions, usages et effets de l’intersectionnalité.
http://id.erudit.org/iderudit/ 1029274ar
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; EDI; amérique du nord; amériques; approches et analyses; canada; femmes* immigrantes; femmes* racisées; formations; intersectionnalité; militance; montréal; organisations féministes; outils; périodes historiques; québec; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques

Beyond the birds and the bees: A study of comprehensive sex education in Oregon high shools - Wicks, Katie J. (Oregon State University, 2014)
Oregon high schools are required to provide comprehensive sex education to students, but there is anecdotal evidence that this is not consistently being carried out across all schools. Despite the significant amount of literature that exists on the topic of sex education, there is a gap in regards to what is being done in Oregon on the application of the sex education policy in schools and on what students want to learn in high school sex education programs. This study is intended to fill that gap in order to enhance the knowledge pool pertaining to the sex education needs of high school students in Oregon. An anonymous online survey was conducted of first-year Oregon State University students between the ages of 18-20. Upon reviewing the results it appears that Oregon’s sex education policy is being carried out in schools, but perhaps not as completely as it should be. It also appears that there is a discrepancy between what students are being taught and what they feel is important to be taught. In doing this research it has become clear that in order to best meet the needs of youth, sex education programs in Oregon high schools need to be more comprehensive and inclusive.
https://ir.library.oregonstate.edu/concern/honors_college_theses/8p58pg03f
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; LGBTQIA2+; amériques; approches et analyses; identités LGBTQIA2+; inclusion; intersectionnalité; mémoires/thèses; oregon; périodes historiques; queer; ressource en ligne; régions géographiques; sexualité; thématiques; école secondaire; éducation sexuelle